Unveiling the burden: prevalence and predictors of psychological distress among domestic workers in Kigali‑Rwanda - Favina, Alain; Turatsinze, Everest; Lutasingwa, Dan; Abaatyo, Joan; Mulisa, Fred; Mukashyaka, Ritah; Kansiime, Deborah; Hobe, Nicholas; Ngabo, Octave; Rukanikigitero, Jean Marie Vianney; Ochora, Moses; Gutabarwa, Louange Twahirwa; et al. (Discover Mental Health, 2024)
Background: Psychological distress is becoming more prominent among employees in various workplaces, and domestic work may not be an exception. This study aimed to determine the prevalence of psychological distress and associated factors among domestic workers in Rwanda. Methods: This cross-sectional study captured data from 870 domestic workers in Kigali City, Rwanda. Psychological distress was measured using questions from the Kessler Psychological Distress Scale (K10). Binary Logistic regression analyses were used to ascertain the factors associated with psychological distress. Results: The prevalence of psychological distress was 50.1%. The likelihood of having psychological distress was higher among females, those using substances of abuse, those having over four dependents in the household, and those having worked as domestic workers longer. Conclusion: Half of the domestic workers in Kigali-Rwanda experience distress. To mitigate this burden, awareness of psychological distress among domestic workers and improvement of services to mitigate psychological distress should be increased. These services should particularly target those who are female, with more dependents, who have worked longer in the profession, and who use substances of addiction.
Keywords: Domestic workers; Psychological distress; Substance use; Rwanda; Employment